V460P, variety of popcorn maize for the region of Las Huastecas - Valadez-Gutiérrez Juan; Gómez-Montiel Noel Orlando; Preciado-Ortíz Ricardo Ernesto; Reyes-Méndez César Augusto; Peña-Ramos Alfonso (Revista Mexicana de Ciencias Agrícolas, 2018)
The volume of domestic imports of popcorn maize (Zea mays var. Everta) fluctuates annually between 30 and 40 thousand tons, representing a loss of foreign exchange for the country, with the amount of 300 to 400 million pesos.Giventheneedforproprietarytechnology,INIFAP initiated a national project of breeding popcorn maize, which generated the open-pollinated variety V460P, registered at the National Inspection and Certification of Seeds in 2008 with the number MAZ-1353-190712. The methodology used for the variety V460P was of stratified visual mass selection, applying an adjustment to the selection pressure to include the expansion volume of popcorn per gram of seed, as an additional selection criterion. The variety V460P has a potential for grain yield of 5 t ha-1 under irrigated conditions and 2.3 t ha-1 for rainfed. The area of adaptation covers the region of Huasteca, comprised of the Eastern San Luis Potosí, northern Veracruz and southern Tamaulipas, under irrigation or rainfed. Clay soils and climate AW0. Within an elevation range from 0 to 300 meters. It has an average height of 2.55 m plant, thin stem (10 to 15 mm). From planting to male-f lowering and physiological maturity from 49 and 119 days, respectively. It has excellent traits to supply the domestic consumption of popcorn.